2018
DOI: 10.15294/jvce.v3i1.13424
|View full text |Cite
|
Sign up to set email alerts
|

Development of Learning Model of Project-Based Learning Integrated with Entrepreneurship in The Productive Learning of Motorcycle Tune-Up Competence

Abstract: Unemployment of graduates of Automotive Engineering expertise program of Vocational High School (SMK) can be overcome with entrepreneurship. The obstacle is that students are not ready to become entrepreneurs. Learning process at school needs to be analyzed to find new learning models that enhance students' entrepreneurship skills which is in accordance with the expertise program. This study aims to analyze the factual conditions of productive learning of motorcycle tune-up competence and entrepreneurial learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…In addition, graduates must be able to work together in teams. To fulfill this ability, students must be given opportunities to group structured as a team, one of which is to use a model of project-based learning [4]. Therefore, when the graduates work in the future, they will be able to interact with various educational backgrounds, ethnicities and races in the oil and gas industry [5].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, graduates must be able to work together in teams. To fulfill this ability, students must be given opportunities to group structured as a team, one of which is to use a model of project-based learning [4]. Therefore, when the graduates work in the future, they will be able to interact with various educational backgrounds, ethnicities and races in the oil and gas industry [5].…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that there was increased student motivation and enhanced learning outcomes after the model's usage. In addition, Ariwibowo, Slamet and Syamwil (2018) developed and implemented an instructional model based on PBL that integrated entrepreneurship and productive learning of motorcycle tune-up competence. The researchers found that students' technical and entrepreneurship skills in the class that implemented the model increased significantly.…”
Section: Related Literaturementioning
confidence: 99%
“…Pada model Learning Cycle 5E ini guru akan berperan sebagai fasilitator kegiatan belajar siswa , berupaya untuk memanfaatkan lingkungan baik di dalam maupun di luar kelas serta dapat mengevaluasi setelah proses pembelajaran dilaksanakan. [25].…”
Section: Abstrakunclassified